Measuring inflammation in paediatric severe asthma: biomarkers in clinical practice - Licari, Amelia (Breathe (Sheff), 2020)
Severe asthma in children is a highly heterogeneous disorder, encompassing different clinical characteristics (phenotypes) and immunopathological pathways (endotypes). Research is focusing on the identification of noninvasive biomarkers able to predict treatment response and assist in designing personalised therapies for severe asthma. Blood and sputum eosinophils, serum IgE and exhaled nitric oxide fraction mostly reflect type 2 airway inflammation in children. However, in the absence of available point-of-care biomarkers, the diagnosis of non-type 2 asthma is still reached by exclusion. In this review, we present the most recent evidence on biomarkers for severe asthma and discuss their implementation in clinical practice. We address the methods for guiding treatment decisions and patient identification, focusing on the paediatric age group. KEY POINTS: Severe asthma in children is a highly heterogeneous disorder, encompassing different clinical characteristics (phenotypes) and immunopathological pathways (endotypes). Research is focusing on the identification of noninvasive biomarkers able to predict treatment response and assist in designing personalised therapies for severe asthma. Blood and sputum eosinophils, serum IgE and exhaled nitric oxide fraction mostly reflect type 2 airway inflammation in children. However, knowledge regarding non-type 2 inflammation and related biomarkers is still lacking. EDUCATIONAL AIMS: To summarise the most recent evidence on biomarkers for severe asthma in children. To discuss their implementation in clinical practice through guiding patient identification and treatment decisions.